The Problems in Professional Competence of Teachers in Teaching English Subject at Vocational High Schools - Syamsinar Syamsinar; Baso Jabu (ELT Worldwide: Journal of English Language Teaching, 2015)
This research was intended to investigate the problems in professional competence faced by the English teachers of vocational high schools in Gowa, South Sulawesi, Indonesia. This research applied descriptive qualitative method. The data were collected by using three instruments: questionnaire, interview and observation checklist. The participants were two experienced English teachers, two inexperienced English teachers, and eight students. The professional competence indicators are adapted from the Regulation of the Minister of National Education of the Republic of Indonesia No. 16/2007. The results of this research reveal that the teachers' problems dealing with professional competence in teaching English at vocational high schools include (a) problem in mastering the materials, (b) problems in mastering the curriculum, (c) problem in developing materials creatively, (d) difficulties in developing the teacher professionalism continuously, (e) problems in using the information technology and (f) problems of classroom management. Keywords:  professional competence, experienced English teachers, inexperiencedEnglish teacher.